2018
DOI: 10.1111/rda.13347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red propolis extract isolated or encapsulated in nanoparticles on the in vitro culture of sheep preantral follicle: Impacts on antrum formation, mitochondrial activity and glutathione levels

Abstract: Contents This study aimed to characterize the hydroethanolic extract of red propolis (HERP) and nanoparticles containing HERP for using as an additive in the culture medium of isolated ovine preantral follicles. HERP was characterized by high‐performance liquid chromatography (HPLC) and determination of flavonoid content, and the nanoparticles by the mean particle diameter, polydispersity index (PI) and encapsulation efficiency (EE). The effect of HERP (10 and 20 ηg/ml—HERP10 and HERP20 groups) and nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The propolis extract was prepared according to a previously reported protocol [ 14 ], where 120 g of propolis powder in 1380 mL ethanol 70% was sonicated for three hours at room temperature (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The propolis extract was prepared according to a previously reported protocol [ 14 ], where 120 g of propolis powder in 1380 mL ethanol 70% was sonicated for three hours at room temperature (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Scenarios associated with enhanced 2-hydroxybutyric acid release may be associated with increased liver glutathione synthesis from methionine as necessary for detoxification functions, suggesting the beneficial cardiac effects of propolis in parkinsonian rats treated with this bee-derived product. Research has shown that propolis protects cell plasma membrane and attenuates the effects of oxidative stress ( Nascimento et al, 2018 ; Laaroussi et al, 2021 ; Nna et al, 2021 ). The animals in the 6-OHDA group showed a decrease in the concentration of 2-hydroxybutyric acid in the heart and studies performed in autopsies of humans with PD and in animal models of the disease described a decrease in glutathione content and/or activity as a common finding in PD ( Aoyama and Nakaki, 2012 ; Mazzetti et al, 2015 ; Dwivedi et al, 2020 ; Aoyama et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scenarios associated with enhanced 2hydroxybutyric acid release may be associated with increased liver glutathione synthesis from methionine as necessary for detoxification functions, suggesting the beneficial cardiac effects of propolis in parkinsonian rats treated with this beederived product. Research has shown that propolis protects cell plasma membrane and attenuates the effects of oxidative stress (Nascimento et al, 2018;Laaroussi et al, 2021;Nna et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Nanoparticles synthesized with plant extracts have successfully been used in culture systems for preantral follicles. Nascimento et al (2019) reported that nanoparticles functionalized with hydroethanolic extract of red propolis increased glutathione (GSH) levels, mitochondrial activity, and antrum formation in ovine preantral follicles cultured in vitro . GSH is a tripeptide formed by amino acids cysteine, glycine, and glutamine, which plays an important role in combating oxidative stress (Adeoye et al, 2018).…”
Section: Effects Of Nanoparticles On In Vitro Cultured Preantral Folliclesmentioning
confidence: 99%
“…| EFFECTS OF NANOPARTICLES ON IN VITRO CULTURED PREANTRAL FOLLICLESNanoparticles synthesized with plant extracts have successfully been used in culture systems for preantral follicles Nascimento et al (2019). reported that nanoparticles functionalized with hydroethanolic extract of red propolis increased glutathione (GSH) levels, mitochondrial activity, and antrum formation in ovine preantral follicles cultured in vitro.…”
mentioning
confidence: 99%